Cerebellar Progressive Multifocal Leukoencephalopathy Mimicking Anti-Yo-Antibody-Associated Rapidly Progressive Cerebellar Syndrome - Takayoshi Akimoto; Makoto Hara; Satoshi Hirose; Kazuo Nakamichi; Hideto Nakajima (MDPI AG, 2023)
A 58-year-old woman with a history of systemic lupus erythematosus (SLE) who was taking prednisolone and mycophenolate mofetil presented with gait disturbances that progressively worsened over a period of 3 months. Her blood test and cerebrospinal fluid (CSF) examination results did not indicate active SLE. Initial brain magnetic resonance imaging (MRI) revealed a small spotty lesion in the left cerebellar peduncle. The clinical course was consistent with rapidly progressive cerebellar syndrome (RPCS), which sometimes involves neuronal antibodies. The line blot assay detected anti-Yo antibodies, but no malignancy was found. Immunohistological techniques using rat brain sections yielded a negative result for anti-Yo antibodies. The second MRI revealed a focal lesion and surrounding spotty lesion in the left cerebellar peduncle, which was consistent with the punctate pattern observed in progressive multifocal leukoencephalopathy (PML). The CSF JCV-DNA test indicated the presence of cerebellar PML. Immunosuppressants were reduced, and mefloquine and mirtazapine were initiated. After approximately 2 years and 1 month, the CSF JCV-DNA results became negative. Cerebellar PML may exhibit a clinical course that is consistent with RPCS. The punctate pattern should be recognized as an early manifestation of PML. The CSF JCV-DNA copy number may serve as a useful indicator of PML stabilization.